Application of the Hydropower Sustainability Assessment Protocol in the Zambezi River Basin - World Bank (World Bank, Washington, DC, 2019)
The World Bank has been supporting a comprehensive program to strengthen cooperative management and development within the Zambezi River Basin. This program provides regional financing and analytical work that brings together the various commitments within a World Bank-financed portfolio of more than USD 2  billion to facilitate dialogue among the riparian states and further drive the development of climate-resilient water resources for sustainable growth. The application of the Hydropower Sustainability Assessment Protocol in the Zambezi River Basin represents part of this broader program of support to the riparian states toward enhancing development outcomes through improved cooperation and sustainable development. The Hydropower Sustainability Assessment Protocol is a multi-stakeholder tool that evaluates the performance of hydropower projects against globally-applicable sustainability criteria for basic good practice and proven best practice. This Program Report reflects on the project design, objectives, results, and lessons learned from the experience of using the Protocol for guided self-assessment with three hydropower operators in the basin: the Zambezi River Authority, Zesco, and Hidroeléctrica Cahora Bassa.